Perencanaan dan Penganggaran Perusahaan sebagai Instrumen Manajemen Strategis: Studi Literatur - Mutia Adeliana P.; Jonrian Simamora; Nabila Balqis (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
Planning and budgeting are fundamental components in corporate management that play a crucial role in shaping business direction and sustainability. Planning serves as the foundation for setting objectives and strategies, while budgeting translates these plans into measurable resource allocations. The integration of both enables organizations to operate in a more structured, efficient, and controlled manner. Furthermore, effective implementation of planning and budgeting enhances decision-making quality, strengthens coordination across departments, and reduces the risk of resource inefficiency. In practice, these aspects are closely linked to accounting, financial management, and strategic management, making them integral elements of the overall management system. Through a data-driven and adaptive approach, planning and budgeting support organizations in responding to dynamic business environments and maintaining long-term financial stability.